HUBUNGAN INFEKSI SOIL TRANSMITTED HELMINTH (STH) TERHADAP KARAKTERISTIK MASYARAKAT LINGKUNGAN SEKITAR PETERNAKAN DI DAERAH KLUMPANG KAMPUNG KECAMATAN HAMPARAN PERAK - Situmeang, Suryani M.Florence; Dewi Setiyawati; Suparni (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Worm disease is a common people disease commonly encountered in areas, infections can occur simultaneously by several types of worms atonce. For children, the worm disease will have an inmpact for the impaired learning ability, and for adult will decreasing the work productivity. At the North Sumatra, especially Medan City, prevalence of worms in children around (60-70%) of all cases. Research on Soil Transmitted Helminth (STH) Infectious Relationship to Characteristic of Livestock Environment Community in Klumpang Kampung Kecamatan Hampatan Perak, conducted on March-June 2023 at Parasitology Laboratory Poltekkes Medan the department of the medical laboratory technology of Health with using eosin 2% method, with population of 26 samples . The research was analytic observational using cross sectional design. The data obtained were analyzedusing chi-square test at 95% confidence level (?= 0,05). Based on study about Connection Infection Soil Transmitted Helminth (STH) Against Characteristics of Environmental Societies Around Livestock in Klumpang Kampung District Silver Obstacle , obtained results of the 26 samples identified 5 infected samples were found worm Ascaris lumbricoides (20%), with connection STH infection against age 19.2 % only experienced by children just . There's a relationship STH infection against type gender . There's a relationship between education with STH infection . There's a relationship between work with STH infection